Effect of Dissemination of Resources and Information Method for Overnutrition Prevention Behavior on Primary School Children in Makassar (Medico Legal Update, 2021)
The prevalence of overnutrition among primary school aged children, which ranges from the risk of obesityglobally including Indonesia, is currently increasing. This study aimed to assess the difference in behaviorchange in physical activity and habit of soft drinks consumptions before and after the intervention withthe dissemination method of resources and information. The research was conducted at primary schools inMakassar City. This research used a Quasy Experiment approach with a pretest and post-test examinationthrough control group design. The study was conducted for 3 months by providing health information relatedto overnutrition and obesity while monthlyvisit or monitoring of children was carried out using a 24 hourfood recall. The sampling technique was carried out by means of proportional random sampling. Data wereanalyzed by univariate, bivariate, and multivariate analysis. The results showed that there was an effect ofdissemination of resources and information on physical activity (p = 0.000) and soft drink consumptionhabits (p = 0.000) before and after the intervention. The conclusion is that the application of the method ofdissemination of resources and information is effective in changing the behavior of preventing overnutritionin primary school children. It is expected that efforts in schools such as the method of dissemination ofresources and information with peer education will become a reference in efforts to prevent more nutritionin improving students’ healthy eating patterns through dissemination of resources and information.